The codification of Islamic criminal law in the Sudan. Penal codes and Supreme Court case law under Numayri and al-Bashir - Köndgen, Olaf. (Studies in Islamic Law and Society, 2018)
In The Codification of Islamic Criminal Law in the Sudan , Olaf Köndgen offers an in-depth analysis of the Sudan's Islamized penal codes of 1983 and 1991, their historical, political, and juridical context, their interpretation in the case law of the Supreme Court, and their practical application. He examines issues that arise in sharīʿa criminal law, including homicide, bodily harm, unlawful sexual intercourse ( zinā , liwāṭ ), rape, unfounded accusation of unlawful sexual intercourse ( qadhf ), highway robbery ( ḥirāba ), apostasy ( ridda ), and alcohol consumption. Drawing on a wide range of primary and secondary sources, a large number of previously untapped Supreme Court cases, and interviews with judges and politicians, Köndgen convincingly explains the multiple contradictions and often surprising aspects of one of the Arab world's longest lasting applications of codified sharīʿa criminal law. Olaf Köndgen won the DAVO Dissertation Prize 2014 for his Ph.D. thesis. \'This extremely well-documented study represents a milestone for the discussion of Islamic criminal law in the Muslim world as a whole and in the Sudan especially. Olaf Köndgen fills an academic void; his work deserves the greatest recognition, for its extraordinary quality, its thoroughness and systematic approach.\' Prof. Günter Meyer, Johannes Gutenberg University Mainz